2004
DOI: 10.1023/b:pham.0000022418.80506.9a
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Phage Display to Identify M Cell-Targeting Ligands

Abstract: In summary, we have identified novel ligands that target M cells and Peyer's patch tissue, and thus may have utility in the targeted oral delivery of vaccines and vaccine carrier systems to the mucosal immune system within the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Among them, phage display approaches have shown great potential for isolating antibodies or peptides that recognize specific target molecules, such as vascular endothelial growth factor (22), α v β 3 integrin (23,24), NF-κB (25), and p53 (26,27). Many studies have shown that tissue-specific peptides can be isolated with no prior knowledge of the tissue profile by in vivo phage display technology (28,29). The homing peptides screened by in vivo phage display have revealed an unexpected degree of diversity of blood vessels (30).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, phage display approaches have shown great potential for isolating antibodies or peptides that recognize specific target molecules, such as vascular endothelial growth factor (22), α v β 3 integrin (23,24), NF-κB (25), and p53 (26,27). Many studies have shown that tissue-specific peptides can be isolated with no prior knowledge of the tissue profile by in vivo phage display technology (28,29). The homing peptides screened by in vivo phage display have revealed an unexpected degree of diversity of blood vessels (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, gastrointestinal administration of proteins, in the absence of adjuvants, preferentially induces immunological tolerance ("oral tolerance") 1 , but adjuvant-including enteric vaccines are superior in inducing IgA responses which are important to prevent infections with 4 targeting [13][14][15] and receptor identification 16,17 . Extensive screening of phage display libraries has also been used to identify ligands that facilitate translocation across the mucosa of the gastrointestinal tract 18 or binding to and transport via M cells 19,20 or goblet cells 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ligands targeting human papillomavirus, which were selected through biopanning against human papillomavirus 16-transformed SiHa cells, could deliver cargo molecules to the target cells (29). Moreover, ligands against PPs, the gut epithelium, or polymeric IgRs for vaccine or drug delivery into the mucosal area were isolated using a biopanning approach, although the efficiency of Ag delivery was tested only in an in vitro cell culture system (30)(31)(32). In a previous study, we showed that oral vaccination using the GM1 ganglioside-targeting ligand, which was selected from panning of a phage display library, induced increased mucosal and systemic immune responses against a ligand-fused Ag (33).…”
mentioning
confidence: 99%